Health in the Era of the Internet of Things – A Smart Health Information System Architecture - Strobel, Gero; Perl, Juliane (Proceedings of the 24th Pacific Asia Conference on Information Systems (PACIS), 2020)
Health and well-being have been among the essential needs of humanity since the beginning of time. The healthcare systems are coming under more and more pressure due to a constantly growing world population, demographic change and steady rising of chronic disease rates. Through these circumstances, traditional healthcare systems may soon reach their limits and medical resources are becoming an increasingly valuable commodity. Modern technologies like the Internet of Things offer based on their application possibilities great potential for increasing among others flexibility, efficiency and cost-effectiveness of the healthcare system. To ensure such an IoT based healthcare for patients, holistic information and communication technology solutions are required that integrate both system-relevant technological and human aspects. Against this background, we present a generic information system architecture for smart health systems, based on a systematic literature driven explorative analysis of the domain.
Keywords: e-health; Smart Health; Internet of Things; Information System; Information System Architecture